KOMPETENSI SOSIAL GURU IPS TERPADU DI SMP ADABIAH PADANG - Armaisya, Nicke - (Pendidikan Sejarah, 2014)
Background of the study was to reveal the social competence of integrated social studies teacher in Padang junior high school Adabiah. This is study aims to deterinine the social compefence of integrated in Padang junior high social studies teacher Adabiah qualitative research respondents in the study is the principal, vice-principal, teacher and student assemblies in Padang junior high school Adabiah fields of research data collection was conducted interviews and then the data is processed by an interactive analysis techniques the result showed that the social competence of teachers integrated social in Padang junior high school (1) integrated social studies teacher social competence in interacing degan students based on oral communication, writing and gusture, of the four theacher only two teachers who are less able to communicate with the students gesture. Using information and communication technology are furctionally integrated social sciences found that the teachers had difficulty in using information and communication technology as medium of learning activities communicate and interact effectively in general it can be concluded that the junior high school social studies teacher Adabiah able to communicate and get along with learners. (2) integrated social studies teacher social competence in integracing with cowokers fellow teachers can not communicate ewees using information and communication technology in general functionally integrated social studies teachers have difficulty in using communicate and interact effectively in general it can be concluded that the junior high school social studies teacher Adabiah can communicate with a fellow teacher colleagkes based on this study it can be concluded that the social competence of integrated social can be said to be less capable in social competence in oral written and cues using technology and communications funivctionality and communicate and interact effectively.